133k views
3 votes
Find p(–4) if p(x) = x ^3 – 3x^ 2 + 7x + 6.

1 Answer

6 votes

Answer:

p(-4) = -134

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation

Explanation:

Step 1: Define

p(x) = x³ - 3x² + 7x + 6

p(-4) is x = -4

Step 2: Evaluate

  1. Substitute in x [Function]: p(-4) = (-4)³ - 3(-4)² + 7(-4) + 6
  2. Evaluate exponents: p(-4) = -64 - 3(16) + 7(-4) + 6
  3. Multiply: p(-4) = -64 - 48 - 28 + 6
  4. Subtract: p(-4) = -140 + 6
  5. Add: p(-4) = -134
User Runmad
by
5.8k points